ANALISIS POLA PENGGUNAAN LAHAN DI DAERAH ALIRAN SUNGAI (DAS) SA’DAN KABUPATEN TANA TORAJA - D Maemunah Dawy (Bumi Lestari Journal of Environment)
The purposes of this research are to know the land use pattern. To analyze the potency of land todetermine the optimal land use pattern in relation, with the management of Sa’dan Watershed at Tana TorajaRegency,The research is carried out at at Sa’dan watershed of Tana Toraja Regency which include 24 villages.The methods used are qualitative and quantitative descriptive. The primary data is collected by survey ormapping method and questionnaire, meanwhile the secondary data is obtained from related departments. Thecolleted data are then analyzed by statistical and Geographical information System (GIS).The result of the analysis show that; 1) The condition of land use pattern at Sa’dan watershed haschanged its function; 2) the degradation of land causing erosion is ampunt of 64.053,69 ton/ha/year; 3) theimplementation for the change of land use pattern recommended is reducing the erosion quantity in eachtreatment, namely 281,19 ton/ha/year, 276,87 ton/ha/year, 4.201,66 ton/ha/year and 383,40 ton/ha/year in thefirst, second, third and fourt freatments.Based on the analysis result, some effort could be done in order to reduce the land degradation and theoptimal land use were as follws; 1) the land use pattern should be changed: 2) the land conservation systemshould be implemented exaltly and quickly; and 3) the participation of the government, private sector, nongovernmentsocial organozation, and society in relative to the management of Sa’dan W atershed of TanaToraja Regency should be also involved.